Fetterman, David M. 2019. Ethnography Step by Step: An Ethnography Field Guidebook. California. SAGE Publications, Inc. 224 pages. ISBN: 9781452255651 - Sulistiyawan, Andrik (International Journal Ethnic, Racial and Cultural Heritage, 2025)
The original title of this book is "Ethnography: Step by Step (Fourth Edition)" written by David M. Fetterman, an experienced practitioner and professor of anthropology. David"™s work not only provides a detailed step-by-step guide to conduct ethnographic research but also offers insightful conceptual and theoretical discussions alongside contemporary issues. It is no wonder that the book may fill the lack of the Indonesian language (bahasa Indonesia) book on ethnographic research methods, hence I recommend this book to all Indonesian ethnographers and anthropologists who teach ethnographic research and writing.